Estrutura formal e redes sociais informais: um estudo comparativo entre organização pública e privada - Nishi, Juliana Mayumi (2014)
The aim of this multi-cases study was to analise the influence of formal structure in the emergence of Informal Social Networks in public and private organizations. The study was carried out in a public and a private school in order to determine the implications, attitudes, and behaviors of individuals inserted in the two contrasting situations. Regarding the nature of the investigation, this is a qualitative and quantitative research and the nature of the study outlines a descriptive approach. To define the organizational structure and the formal relationships of the schools we analyzed documents, performed interviews and made observations. For the mapping and characterization of Informal Social Networks of Information, Friendship and Trust, we used the questionnaire by Kuipers (1999) and Silva (2003), and results were obtained by Ucinet 6.0 software in parallel with NetDraw. Sixty-six employees of the public school were identified as types of flowers and seventy-three employees of the private school were called by names of Brazilian trees. In order to understand the reasons that justify the citation of a specific actor, a semi-structured interview based on Sozen (2012) was performed with all participants. The data analysis was divided into three categories: dependence, motives, and consequences of non-relationship. This way, we could observe the relationship between macro-structural and micro-behavioral power based on the counting of words using the NVivo and SAS softwares. Through the degree of centralization of Informal Social Networks it was possible to identify the central actors and their roles according to the classification of Cross and Prusak (2002). The main findings revealed that the networks of both schools analyzed showed a high potential for relationships to be developed. The size and density of the Informal Social Networks of Information and Trust were higher in the private school, whereas the Informal Social Networks of Friendship was higher in the public school. Although the public school used more informal contacts, the private school had a larger number of groups and cohesive subgroups. We, therefore, verified the influence of the formal structure in the formation of informal relationships, mainly in the private school; however, the strengthening of connections is not only sustained by the duties of the position, but also by the personal qualities of those actors.